Literatur Review: Validitas Dan Reliabilitas Instrumen Perencanaan Karier Siswa Dalam Layanan Bimbingan Konseling - Herman, Pebriani Yusnia; N, Nurfarhanah; Ardi, Zadrian (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Career planning is an important aspect of student development, especially at the high school level where students are in the stage of choosing further education or a career path. Guidance and Counseling (GC) plays an active role in assisting students with career planning through effective and well-targeted assessment services. This study uses a literature review method to examine the importance of validity and reliability in developing career planning assessment instruments. The findings show that validity, including content, construct, and criterion validity, as well as reliability, including consistency and stability, are crucial elements in producing accurate and trustworthy assessment instruments. In conclusion, the development of assessment instruments in GC services must consider both validity and reliability aspects to provide a true and consistent picture of students’ potential and career direction.